Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Hung, Po-Chih; Lee, Hsiao-Chien; Lin, Chih-Cheng; Liu, Wen-Hong (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.